New records of Serpulidae (Annelida, Polychaeta) from hydrothermal vents of North Fiji, Pacific Ocean - Kupriyanova, Elena K.; Nishi, Eijiroh; Kawato, Masaru; Fujiwara, Yoshihiro (Zootaxa, 2010)
Serpulidae are sessile suspension-feeding annelids commonly found in the periphery of hydrothermal vents, but up to now only two species, Laminatubus alvini and Protis hydrothermica had been described from such communities. This paper reports two additional serpulid species, collected in 2005 from the North Fiji hydrothermal vent area, identified as Hyalopomatus mironovi and Protis sp. The former has originally been described from the Kurile-Kamchatka Trench and the later recorded from the North-East Pacific. The latter species is similar to Protis hydrothermica, but lacks special finand-blade collar chaetae typical of this genus. Illustrated re-descriptions of the two species have been supplemented by molecular sequences (18S ribosomal RNA). Molecular phylogenetic analyses show that Hyalopomatus mironovi and Protis sp. are sister species of Laminatubus alvini and Protis hydrothermica, respectively.